Sociopragmatic insights into verbal taboos and euphemisms in the Angkola language: A pathway to cultural diplomacy - Jamaluddin Nasution (Universitas Syiah Kuala, 2025)
This study examines the sociopragmatic roles of verbal taboos and euphemisms in the Angkola language, focusing on their function in maintaining cultural diplomacy and social harmony. A qualitative ethnographic approach was employed, with data collected from 320 respondents through observations, in-depth interviews, and online surveys. Respondents represented diverse demographic and occupational backgrounds within the Angkola-speaking regions of North Sumatra. To analyze the data, the study applied thematic analysis, categorizing expressions based on domains such as kinship, religion, body, social status, and supernatural beliefs. The findings reveal a high level of awareness about verbal taboos within the Angkola community, yet these practices are under threat due to the impact of globalization and technological advancements. The research identifies key challenges in the transmission of these cultural norms to younger generations, who are increasingly detached from traditional linguistic practices. The implications of this study emphasize the need for integrating indigenous languages and cultural education into school curricula, as well as leveraging media and digital platforms to promote cultural preservation. This research provides a foundation for further investigation into the role of language in cultural sustainability and offers practical strategies for safeguarding endangered linguistic traditions in the modern era.